2008
DOI: 10.2166/wst.2008.477
|View full text |Cite
|
Sign up to set email alerts
|

The secret to achieving reliable biological phosphorus removal

Abstract: The enhanced biological phosphorus removal (bio-P) activated sludge process has a reputation for variable performance. A significant factor contributing to variability in bio-P was found to be related to microbial population dynamics involving the competitive growth of polyphosphate accumulating organisms (PAOs) and glycogen accumulating organisms (GAOs). It was found that the key factor in their competitive growth was the specific type of VFA in the influent to the bioreactor. The PAOs seem to have a competit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Since the findings of Cech and Hartman (1993) concerning the G-bacteria, a major focus of EBPR microbiological research has been competition between PAOs and GAOs. While some operational parameters are known to cause upset and deterioration of EBPR (Scruggs et al, 2003;Stephens and Stensel, 1998;Thomas et al, 2003), GAO proliferation has been blamed primarily for impairment of the EBPR process (Thomas, 2008;Vaboliene and Brazenaite, 2009). Thus, understanding the mechanisms of how PAOs and GAOs compete and the circumstances that favor GAO growth have become increasingly important.…”
Section: Competition Between Polyphosphate-and Glycogen-accumulating mentioning
confidence: 99%
See 1 more Smart Citation
“…Since the findings of Cech and Hartman (1993) concerning the G-bacteria, a major focus of EBPR microbiological research has been competition between PAOs and GAOs. While some operational parameters are known to cause upset and deterioration of EBPR (Scruggs et al, 2003;Stephens and Stensel, 1998;Thomas et al, 2003), GAO proliferation has been blamed primarily for impairment of the EBPR process (Thomas, 2008;Vaboliene and Brazenaite, 2009). Thus, understanding the mechanisms of how PAOs and GAOs compete and the circumstances that favor GAO growth have become increasingly important.…”
Section: Competition Between Polyphosphate-and Glycogen-accumulating mentioning
confidence: 99%
“…A strategy of alternating feed between acetate and propionate has been used in a number laboratory studies to obtain highly enriched PAO cultures (Saunders et al, 2007;Zhang et al, 2007;Zhou et al, 2008). Based on chemical measurements, Thomas (2008) reported increased stability of a full-scale plant in Australia when an adequate supply of propionate relative to acetate was provided. However, this strategy has been contradicted by many studies of full-scale EBPR plants.…”
Section: Competition Between Polyphosphate-and Glycogen-accumulating mentioning
confidence: 99%
“…Thomas (2008) The COD must have a sufficient portion of VFAs. Increasing pH could give an advantage to PAOs, while alkaline conditions inhibited GAO proliferation without affecting PAO metabolism.…”
Section: Whang and Park (2006)mentioning
confidence: 99%
“…VFAs and in particular acetic acid has long been regarded crucial for successful operation of enhanced biological phosphorus removal in WWTPs as they are key substrates for several phosphorus accumulating organisms (PAO). In addition, recent investigations have shown that the presence of propionic acid may be important for PAOs to gain a competitive advantage over glycogen accumulating organisms (GAOs) (Thomas, 2008). Figure 4 shows total VFA concentrations, measured during the 9 experiments in reactor R6, where 48 hours of anaerobic conditions were maintained.…”
Section: Chemical Analysesmentioning
confidence: 99%